The Government Legal Warranty for Consumers in The Purchase of Property in Indonesia - Subekti, Subekti; Sidarta, Dudik Djaja; Marwiyah, Siti; Suyanto, Suyanto; Ismail, Nazli bin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The sale and purchase of houses between developers and buyers often result default, which detrimental to consumers. The state has issued various policies regarding buying and selling houses and legal guarantees for buying and selling houses, but violations still occur and there is no legal guarantee from the state but must be resolved through litigation.Purposes of the Research: The purpose of this study is to analyze and find problems with house sale and purchase contracts based on the Sale and Purchase AgreementMethods of the Research: The method used in this research is normative juridical. The research used is library research. The basis used in this research is the juridical basis consisting of Law Number 1 of 2011, GovernmentRegulation Number 12 of 2021. Results of the Research: When the state issues permits to operate housing to developers, the state has provided a legal guarantee to protect its people. Due to the guarantees that have given by the Government through statutory regulations and consumers following the instructions, they are guaranteed to receive legal protection from the state, State Administrative Officials, in terms of granting permits they have gone through applicable legal procedures, if it is proven otherwise then the government must be responsible for the decision. State Administration. However, if there is a violation of the law by the developer, it will difficult for home buyers to claim losses. Experienced, meaning that at the implementation level there is no guarantee for buyers from the state.